The Influence of Organizational Culture, Work Environment, Psychological Capital, and Employee Empowerment on Organizational Commitment: Study on Private Employees in Solo Raya - Dian Eva Kumala; Gustita Arnawati Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine and analyze the influence of organizational culture, work environment, psychological capital, and employee empowerment on organizational commitment. This research was conducted on private company employees in Solo Raya using a quantitative method with 190 respondents. Data were collected through questionnaire distribution, and the data analysis used was multiple linear regression analysis. The results of this study indicate that organizational culture has no effect on organizational commitment, work environment has no effect on organizational commitment, psychological capital has a positive and significant effect on organizational commitment, and employee empowerment has a positive and significant effect on organizational commitment.